2018
DOI: 10.17576/jsm-2018-4712-08
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Transcriptional Regulatory Network in Arabidopsis thaliana Aliphatic Glucosinolate Biosynthetic Pathway

Abstract: Aliphatic glucosinolate is an important secondary metabolite responsible in plant defense mechanism and carcinogenic activity. It plays a crucial role in plant adaptation towards changes in the environment such as salinity and drought. However, in many plant genomes, there are thousands of genes encoding proteins still with putative functions and incomplete annotations. Therefore, the genome of Arabidopsis thaliana was selected to be investigated further to identify any putative genes that are potentially invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…UV-A radiation could stimulate the biosynthesis and accumulation of GLs in Chinese kale, which might be caused by the activation of transcription factor genes such as HY5, after the UV-A photoreceptor senses the signal. HY5 could regulate the transcription levels of sulfur assimilation genes ATPs, APK and APR, and then affect the expression of glucosinolates biosynthesis genes, e.g., SOT16, SOT17, SOT18, MAM-L, CYP79F1 and CYP79B2 [64]. From the results of this study, GLs con-tents significantly increased under UV-A might attribute to that UV-A could up-regulate the gene expressions of the key enzymes related to glucosinolates metabolites [65,66].…”
Section: Discussionmentioning
confidence: 59%
“…UV-A radiation could stimulate the biosynthesis and accumulation of GLs in Chinese kale, which might be caused by the activation of transcription factor genes such as HY5, after the UV-A photoreceptor senses the signal. HY5 could regulate the transcription levels of sulfur assimilation genes ATPs, APK and APR, and then affect the expression of glucosinolates biosynthesis genes, e.g., SOT16, SOT17, SOT18, MAM-L, CYP79F1 and CYP79B2 [64]. From the results of this study, GLs con-tents significantly increased under UV-A might attribute to that UV-A could up-regulate the gene expressions of the key enzymes related to glucosinolates metabolites [65,66].…”
Section: Discussionmentioning
confidence: 59%
“…It also highlighted the in silico-based approaches that employed the ‘guilt-by-association’ (GBA) principle in identifying transporters in plant specialised metabolism. In relation to GSL biosynthesis, the GBA approach has been used to identify regulators [ 50 , 51 , 52 , 53 , 54 , 55 ] and enzymes [ 56 , 57 , 58 , 59 ]. Identifying TPs using co-expressed genes successfully defined a boron transporter candidate in A. thaliana [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose a ‘guilt-by-association’ (GBA) approach to identify and characterise possible GSL TPs involved in GSL metabolism [ 32 ]. The GBA principle has been used to identify regulators [ 50 , 51 , 52 , 53 , 54 , 55 ] and enzymes [ 56 , 57 , 58 , 59 ] involved in GSL biosynthesis. Detailed information on most of the molecular components related to GSL biosynthesis and metabolism can be found in SuCComBase, which is accessible at (accessed on 16 December 2021) [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that GSL biosynthesis is a complex process, which is regulated by multiple layers comprising genetic sites, developmental processes, transcription, and synthetic products ( Barco and Clay, 2019 ; Meier et al, 2019 ). At present, the biosynthetic framework roadmap of GSL is basically clear in A. thaliana , and most regulatory genes in related pathways are known, but the specific functions of these regulatory genes are not fully elucidated ( Ashari et al, 2018 ; Vo et al, 2018 ). In this process, MYB transcription factors play an important role in the regulation of GSL formation.…”
Section: Future Workmentioning
confidence: 99%